2,7-Carbazole Derived Organoboron Compounds: Synthesis and Molecular Fluorescence - Chen, Minhui; Wei, Juan; Zhang, Yufeng; Wu, Lin; Tan, Leibo; Shi, Shanglong; Shi, Junqing; Ji, Lei (Frontiers in Chemistry, 2021)
Triarylboranes have drawn much attention in OLEDs owing to their remarkable solid-state luminescence properties. Here two new A-D-A type compounds, 2,7-bis(dimesitylboryl)-N-ethyl-carbazole (BCz) using triarylborane as electron acceptor and carbazole as electron donor while 2,7-bis((4-(dimesitylboryl)phenyl)ethynyl)-9-ethyl-carbazole (BPACz) using phenylacetylene as extra conjugated bridge, have been synthesized and their photoluminescence related properties in various states have been investigated both experimentally and theoretically. Both compounds show blue emission with high quantum yields, being potential candidates for blue OLED materials.